Effect Of Substitution For Gamal Leaf Flour (Gliricidiasepium) With Rations Commercial On Quail (Coturnix-Cortunix Japonica) Carcass Composition - Bagaskara, Dwi Angga; Anggraeni,; Wahyuni, Dewi (Jurnal Peternakan Nusantara, 2025)
Quail is a type of poultry that is popular because compared to broiler chickens, quail grow faster. This research aims to test the influence Substitution of gamal leaf flour (Gliricidia sepium) in feed on quail carcass composition. This research was carried out from 28 May to 28 July 2022 at Kandang Poultry, Tri Jaya Farm Sukabumi. This research used 1 (one) day old female quail originating from Pondok Wirausaha Agribisnis Cikembar, Sukabumi. The research design used a completely randomized design (CRD) with 5 treatments and 4 replications. Data were analyzed by ANOVA and Duncan's advanced test. Research treatments R0 = 100% commercial feed (PK), R1 = 99% PK + 1% gamal, R2 = 98% PK + 2% gamal, R3 = 97% PK + 3% gamal and R4 = 96% PK + 4% gamal. Drinking water is provided adlibitum. Observed parameters in study This that is chest and thigh composition, ratio meat with bones and ratios meat with skin on the chest and thighs respectively. The research results show that substitution gamal leaf flour in quail feed is not significantly different (P > 0.05) to chest composition, compoElevsition thighs, ratio meat chest bones and skin as well ratio bones and skin thigh. Research results can conclude that substitution flour leaf gamal 1% to 4% in ration Not yet capable increase chest composition, thighs, ratio meat chest bones and skin as well ratio meat bones and skin thigh. Recommended for research this with substitution flour leaf gamal as feed commercial use 4% level to get percentage more carcasses good